The Effect of Flipped Classroom Model and Learning Styles on Improving Students' Conceptual Understanding: An Experimental Study - Henky Muktiadji; I Nyoman Sudana Degeng; Punaji Setyosari; Dedi Kuswandi; Arina Salsabilla Haq (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: This research aims to explain the influence of the flipped classroom learning model along with learning styles on students' conceptual understanding. Method: This study uses a quasi-experimental method with a 2x2 factorial pretest-posttest non-equivalent control group design involving students from PGRI University Jombang at the undergraduate level.  Results:  The research results reflect that the flipped classroom has a better impact compared to conventional learning. The difference between verbal and visual learning styles is not significant to conceptual understanding. Overall, the use of flipped learning is effective for all types of learning styles in this study in improving conceptual understanding. In practice, the flipped classroom is highly recommended for application in concept comprehension learning with implementation on an LMS and effective discussion features.  Novelty: The novelty of this research lies in the integrative flipped learning model combined with learning styles, which has not been extensively studied for enhancing conceptual understanding.